The Journal of Reference - Julianti Hairani Siregar (LINGUISTICA, 2012)
The paper deals with the analysis of reference based on the theory of Halliday that can be analyzed through any kinds of text. The purposes of this paper are to elaborate the theory, types and retrieval systems of reference.